Occurrence of Chandleronema longigutturata (Nematoda: Acuariidae) in Procyon cancrivorus in the Neotropical region - Alice Graciela Rodriguez Suárez (Revista Brasileira de Parasitologia Veterinária)
Procyon cancrivorus is a wild animal that is found from Central America to Uruguay and northeastern Argentina. It is one of the least studied carnivore species in Brazil. For the purpose of identifying helminths that parasitize P. cancrivorus, individuals of this species that had been run over and killed by motor vehicles were collected from highways in the southern part of the state of Rio Grande do Sul. At necropsy, their organs, along with organ contents and mucous membranes, were examined for parasite collection. The nematodes found in the stomachs of these Procyonidae were cleared with lactophenol and Chandleronema longigutturata was identified. This report provides the first record of occurrences of C. longigutturata in the Neotropical region and its parasitism in P. cancrivorus.